Perancangan Mesin Press Multifungsi Pencetak Cocopot - Faadiyah Cheryl Rachelia; Masri Bin Ardin; Roni Suhartono (G-Tech: Jurnal Teknologi Terapan, 2025)
Coconut fiber has properties that are durable, strong friction, not easily broken, waterproof, resistant to fungi and pests such as termites or rats. Because of this, coconut fiber can be used as handicraft products that have aesthetic value and high selling value. One of the products is cocopot or polybag replacement coconut fiber pot. At this time, the supporting tools in the cocopot production process are still rarely used, especially for MSMEs. To streamline the production process then made the design of multifunction press machine cocopot printer. The methods used in this design are data collection carried out by literature study and observation, making design sketches, making 2D and 3D designs using the Solidworks 2021 application, design validation, monitoring the tool manufacturing process, and evaluation. Cocopot multifunction printer press machine designed to have frame dimensions of 1180mm x 450mm x 745mm with frame material used is UNP iron measuring 80 x 40 x 5 mm. The resulting product is a coconut coir pot with a uniform thickness and is used instead of a polybag with a pot thickness of 1-2mm and is worth selling.This cocopot printing press machine has two different types of press working principles, namely by using a roller press to flatten coconut fiber and a printing press using molding that is driven using an electropneumatic system. The design of the machine is intended to form a cocopot with a tube shape measuring 120mm in diameter with a height of 140 mm.